Investigations on the rheological and swelling-degradation behavior of crumb rubber within the bituminous matrix. (27th February 2023) - Xing, Baodong; Feng, Yelong; Sun, Siwei; Qian, Chengduo; Fang, Chen; Lv, Xiaobo; Song, Aiming; Lyu, Yuchao
Graphical abstract: Highlight: Swelling-degradation behavior in the process of asphalt modification is analyzed. Low asphaltenes benefit the compatibility between polymer phase and asphalt phase. The features of dispersed crumb rubber in the asphalt matrix are revealed. The interaction mechanism between crumb rubber and asphalt binder is disclosed. Abstract: This paper focuses on the rheological and swelling-degradation behavior of crumb rubber within the bituminous matrix. Three different penetration-grade asphalts were modified by crumb rubber in a four-paddle mixer at various curing times and treatment temperatures. Rotational viscosity, dynamic shear rheometer, solubility and gel permeation chromatography tests were conducted to evaluate the viscosity, rheological property, crumb rubber solubility and molecular weight distribution of the rubber-modified asphalts, respectively. Moreover, the microstructure of the rubber-modified asphalts was characterized by fluorescence microscopy and Fourier transform infrared spectroscopy tests. The results reveal that the viscosity and complex modulus of the rubber-modified asphalts decrease and the infiltrating ability of crumb rubber within the bituminous matrix increases with increasing treatment temperature (or curing time). However, serious degradation of crumb rubber and asphalt ageing happen with the increased treatment temperature or prolonged curing time, which causes a noticeable increase in viscosity and stiffness. The increase in asphaltenes content within the bituminous matrix causes an enhancement in viscosity and complex modulus, and releases of the large (or medium) molecules, improving rutting deformation resistance. There is no obvious difference in small molecules, illustrating that asphalt type does not affect the distribution of small molecular size. When the treatment temperature increases from 200 °C to 220 °C, the curing time required to achieve 60 % solubility of crumb rubber in asphalt X is from 25 h to 15 h, which indicates that the higher the treatment temperature, the shorter the curing time required to reach the maximum solubility. Moreover, the swollen crumb rubber molecules are degraded into some small molecule substances dissolving into asphalt binder for modification. It makes the adsorption peaks of typical function groups increase significantly. The outputs from this study can provide the guidance for the selection of preparation conditions and asphalt binders that fabricate the rubber-modified asphalt with desired properties.